Bioenergy intensity and its determinants in European continental countries: evidence using GMM estimation - Alsaleh, Mohammed; Abdul Samad @ Iammi, Abdul Rahim (MDPI, 2019)
This study contributes to the existing literature by examining bioenergy intensity and its related factors in European continental countries (ECC). Through its focus on European continental (EC), this study extends the existing literature, which mainly covers nationwide studies. The current paper aims to investigate the variables of bioenergy intensity in the ECC during the term 2005–2013, construct its economic variables, and evaluate the volume and significance level of the impact of each variable on bioenergy intensity. To successfully achieve this analysis, a generalised method of moments estimator (GMM) was designed for ECC. The estimated models show that available bioenergy for final consumption has a positive impact on bioenergy intensity in ECC. The largest influence on bioenergy intensity was evaluated for the annual growth of Gross Domestic Product (GDP), followed by the investment and referral that the scale and construction of this economic variable should be taken into consideration and applied as a precious bioenergy regulation and policy instruments for developing bioenergy intensity and efficiency.